Disaster, displacement and resilient livelihoods : perspectives from South Asia - Islam, M. Rezaul (Diverse perspectives on creating a fairer society, 2023)
Despite increasing disaster risk in South Asian countries, exposure and vulnerability to natural hazards are not yet at the forefront of development agendas. Covering disaster scenarios, and the causes and consequences of disaster displacement, Disaster, Displacement and Resilient Livelihoods: Perspectives from South Asia provides a much-needed focus on the South Asian context, generating new insights and considering the policy implications of strategies for building resilient livelihoods. Recognising the diversity of South Asian countries in terms of culture, environment, livelihood patterns and socioeconomic and political structures, chapters consider risk landscape and resilience capacity in Afghanistan, Bangladesh, India, Nepal, Pakistan and Sri Lanka. Bringing critical attention to an emerging topic, Disaster, Displacement and Resilient Livelihoods: Perspectives from South Asia breaks fresh ground by considering resilient livelihoods in terms of capacity, resources and policy within each country's diverse local context. Delving into communities' capacities to prevent displacement, their ability to mitigate protection risks during displacement and their options in terms of durable solutions, contributors offer a resilience building framework that incorporates common principles while also retaining a flexibility and adaptability for specific risk environments. Capturing the diverse context of the South Asian resilient livelihood framework, Disaster, Displacement and Resilient Livelihoods: Perspectives from South Asia addresses a crucial gap for an interdisciplinary audience interested in urban and political sociology, social and cultural anthropology and disaster, development and South Asian studies.